Which patients with type 2 diabetes mellitus are perceived as 'difficult' by general practitioners?. Issue 4 (August 2019) - Pentzek, Michael; Santos, Sara; Wollny, Anja; Gummersbach, Elisabeth; Herber, Oliver Rudolf; in der Schmitten, Jürgen; Icks, Andrea; Abholz, Heinz-Harald; Wilm, Stefan
Highlights: High GP-rated 'patient difficulty' is linked to subgroups of male patients. Patients' illness perception is related to GPs' perceived 'patient difficulty'. GPs associate 'difficult patients' with lower adherence and health literacy. Abstract: Aims: To find factors that are associated with a general practitioner's (GP's) subjective impression of a patient being 'difficult' within a sample of patients with type 2 diabetes mellitus (T2DM). Methods: Secondary cross-sectional analysis of a cohort of GP patients with T2DM. GP questionnaire on clinical data and GPs' subjective ratings of patient attributes (including 'patient difficulty'). Patient questionnaire on sociodemographics and illness perceptions. Bivariate and multivariate analyses, adjusted for cluster-effect of GP practice. Results: Data from 314 patients from 49 GPs could be analysed. Independent associations with higher GP-rated difficulty were found for (odds ratio; 95% confidence interval): male patients from male GPs (1.27; 1.06–1.53), unmarried men (1.25; 1.04–1.51), men with non-German nationality (1.80; 1.24–2.61), patients perceiving more problems with diabetes (1.17; 1.04–1.30), patients with higher BMI (1.01; 1.00–1.02) and HbA1c values (1.06; 1.02–1.10), patients being perceived by the GP as less adherent (1.34; 1.22–1.46) and less health-literate (1.19; 1.04–1.35). Conclusions: The impact of patients' gender and illness perception yield new insights into GP-perceived complexity of care. Culturally and gender-sensitive communication techniques for adapting health care goals to patients' problems (rather than norm values) may alleviate GPs' work.